A Science Comic of Urban Metro Structure Performance Evolution and Sensing Control - Zhu, Hehua (Springer Nature Singapore : Imprint: Springer, 2019)
This science comic presents the entire life cycle of the metro system in an accessible and fun way. Just like human beings, a metro system can get sick, and this book introduces its ailments, medical records along with experts' diagnoses and available treatments. Using cartoons, it enables readers of all levels to quickly understand the scientific secrets behind the metro system. It is based on the results of China's 973 program, which aims to promote and develop basic scientific research in China.